Distribution of hydroxyl group in coal structure: A theoretical investigation. (1st February 2017) - Li, Lu; Fan, Hongjun; Hu, Haoquan
Highlights: The most plausible position for hydroxyl group in coal is that with lowest energy. Hydroxyl substituted on the pyridine ring show the most preference. The hydroxyl groups are inclined to form hydrogen bond in coal structure. Abstract: Coal structure is very complicated. The ratio of various functional groups in coal may be studied by existing analysis techniques, but the connections of these functional groups are still mostly unknown. In this work we assume that the most stable position for a certain group could be the most plausible position for that group in the coal structure, then with the help of Density Functional Theory (DFT) calculations we have studied the most plausible position for hydroxyl group in coal. We found the order of preferential position for hydroxyl group is: (1) pyridine rings; (2) polycyclic aromatic hydrocarbons; (3) monocyclic aromatic hydrocarbons; (4) monocyclic heteroatomic molecules (pyrrole, furan and thiophene); (5) alicyclic rings. Besides, double substituted hydroxyl groups on pyridine and polycyclic aromatic ring are possible. Hydroxyl groups tend to be in the positions where they can form hydrogen bond. Electron donating and withdrawing groups do not obviously change the preference of hydroxyl group unless there is hydrogen bond formed.